Disease Transmission Prevention Management of Washing Hands with Soap for Students: Case Study at the University of Jakarta, Indonesia - Wiharto, Mulyo; Puspitaloka Mahadewi, Erlina; Maratis, Jerry; Firmansyah, Agus (Publisher Cv. Inara, 2023)
The present study reports the first comprehensive study on management preventing efforts on disease transmission has been carried out by washing hands with soap since hands are the most transmittable disease medium. Hands should always be clean by using washing hands with soap (CTPS) following to the correct steps. Before practicing CTPS, respondents were given counseling about hand washing by carrying out 7 steps of washing hands starting with rubbing the palms, back of the hands, between the fingers, closing the right and left fingertips, rubbing the thumbs, cleaning the fingertips then ending by wiping the wrists, rinse with water and dry. The results of observations in class action research on 47 respondents that are university students in Jakarta Indonesia concluded that most respondents (59.57%) had practiced CTPS correctly. The results of the observations of the CTPS steps or steps can showed that most respondents (86.02%) have carried out these steps, in fact all respondents have carried out step 1 and step 7 correctly. The quality of the implementation of the CTPS steps, which were mostly good, was made possible by the educational factors possessed by the respondents and the information obtained during the counseling before the respondents carried out the CTPS practices. The good quality of the implementation of the CTPS steps was also made possible that most of the respondents around 74.47% were women.